A wireless RF CMOS interface for a soil moisture sensor - Morais, Raul (2003)
This paper describes a wireless RF CMOS interface for a soil moisture sensor. The mixedsignal interface is based on a 2ndorder switched capacitor, fully differential sigma-delta modulator with an effective resolution of 17-bit. The modulator bit stream output is applied to a counter as a first order decimation filter and encoded as a pulse width modulated signal. This signal is then transmitted by means of an amplitude shift keying modulation, through a power amplifier operating at 433:92 MHz in class-E mode. The soil moisture sensor is based on Dual-Probe Heat-Pulse method and is implemented using an integrated temperature sensor and heater. After applying a heat-pulse, the temperature rise that is a function of soil moisture, generates a differential voltage that is amplified and applied to the mixed-signal interface input. The described interface can also be used with other kinds of environmental sensors in a wireless network for agricultural environments such as greenhouses. The CMOS mixedsignal interface has been implemented in a single-chip using a standard CMOS process (AMI 0.7 um, n-well, 2 metals and 1 poly).